Intercomparison of NOx, SO2, O3, and Aromatic Hydrocarbons Measured by a Commercial DOAS System and Traditional Point Monitoring Techniques - 谢品华 刘文清 付强 王瑞斌 刘建国 魏庆农 (Advances in atmospheric sciences, 2004)
A field-based intercomparison study of a(DOAS) instrument (OPSIS AB, Sweden) andcommercial Differential Optical Absorption Spectroscopydifferent point-sample monitoring techniques (PM, basedon an air monitoring station, an air monitoring vehicle, and various chemical methods) was conducted inBeijing from October 1999 to January 2000. The mixing ratios of six trace gases including NO, NO2, SO2,03, benzene, and toluene were monitored continuously during the four months. A good agreement betweenthe DOAS and PM data was found for NO2 and SO2. However, the concentrations of benzene, toluene,and NO obtained by DOAS were significantly lower than those measured by the point monitors. Theozone levels monitored by the DOAS were generally higher than those measured by point monitors. Theseresults may be attributed to a strong vertical gradient of the NO-O3-NO2 system and of the aromatics atthe measurement site. Since the exact data evaluation algorithm is not revealed by the manufacturer ofthe DOAS system, the error in the DOAS analysis can also not be excluded.